Histone H1 and the origin of protamines - Lewis, John D. (National Academy of Sciences, 2004)
We present evidence that chordate protamines have evolved from histone H1. During the final stages of spermatogenesis, the compaction of DNA in many organisms is accomplished by the replacement of histones with a class of arginine-rich proteins called protamines. In other organisms, however, condensation of sperm DNA can occur with comparable efficiency in the presence of somatic-type histones or, alternatively, an intermediate class of proteins called protamine-like proteins. The idea that the highly specialized sperm chromosomal proteins (protamines) and somatic chromosomal proteins (histones) could be related dates back almost to the discovery of these proteins. Although this notion has frequently been revisited since that time, there has been a complete lack of supporting experimental evidence. Here we show that the emergence of protamines in chordates occurred very quickly, as a result of the conversion of a lysine-rich histone H1 to an arginine-rich protamine. We have characterized the sperm nuclear basic proteins of the tunicate Styela montereyensis, which we show consists of both a protamine and a sperm-specific histone H1 with a protamine tail. Comparison of the genes encoding these proteins to that of a sister protochordate, Ciona intestinalis, has indicated this rapid and dramatic change is most likely the result of frameshift mutations in the tail of the sperm-specific histone H1. By establishing an evolutionary link between the chromatin-condensing histone H1s of somatic tissues and the chromatin-condensing proteins of the sperm, these results provide unequivocal support to the notion that vertebrate protamines evolved from histones.